Evaluation of Metro City Government Website Using WEBUSE Method - Ali Nasution; Dani Apriansyah; Netty Sefriyanti; M S Hasibuan (Prosiding International conference on Information Technology and Business (ICITB), 2021)
Metro City is one of the Madya Cities in Lampung Province which has the goal of "The Realization of an Educated, Healthy, Prosperous and Cultured Metro City". To balance this goal, a facility is needed which is expected to help the community and the government to be able to find and provide information easily and clearly. Metro City has tried to build a forum so that its people can get information easily and clearly, as evidenced by the existence of a metrokota.go.id page. However, the problem isthat many people in Metro City and its surroundings do not yet know the benefits or functions of the website. This is evidenced by the data of respondents filling out thequestionnaire from the percentage of 100% who are natives of Metro City, only 26.8%. So with this basis the Metro City website must be evaluated to find out the shortcomings of the website. This research refers to the Website Usability Evaluation (WEBUSE) approach to determine the results of the usability evaluation on the Metro City Government website with 4 categories of assessment, namely Content Organization and Readability, Navigation And Link, User Interface Design, Performance And Effectiveness. The WEBUSE method used focuses on the development of a webbased usability evaluation system with a subjective action approach that involves the participation of Metro City Government website users to provide an assessment of their website. The purpose of this study is to evaluate whether the Metro City Government website can provide optimal service to users. After measuring WEBUSE, the Metro City Website of the 4 variables measured, in Content organization and readability produces a value of 0.654 "Good", Navigation and link got a value of 0.663 "Good", Performance and effectiveness produces a value of 0.667 "Good", while in user design The interface gets a “Moderate” result with a score of 0.560.Keywords—WEBUSE, Metro City, Website